Monarda fistulosa hydrolate as antimicrobial agent in artificial media for the in vitro rearing of the tachinid parasitoid Exorista larvarum - Dindo, Maria Luisa; Modesto, Monica; Rossi, Chiara; Di Vito, Maura; Burgio, Giovanni; Barbanti, Lorenzo; Mattarelli, Paola (Entomologia experimentalis et applicata, 2021)
Exorista larvarum (L.) (Diptera: Tachinidae), a larval parasitoid of Lepidoptera, can be reared from egg to fecund adult on artificial media composed of crude components. The standard in vitro culture is performed in 24‐well plastic rearing plates. Exorista larvarum eggs, removed from superparasitized larvae of Galleria mellonella (L.) (Lepidoptera: Pyralidae), are individually placed in the wells, each containing a cotton swab soaked in liquid medium. The plates are then sealed until parasitoid puparium formation. To avoid contamination by microorganisms, the artificial medium is routinely supplemented with 0.01% solution of gentamicin. Experiments were carried out to assess whether this broad‐spectrum antibiotic may be replaced with hydrolate of Monarda fistulosa L. (Lamiaceae), which was selected due to its high in vitro activity against pathogenic microorganisms for humans and plants. The hydrolate was either supplemented to the artificial medium (0.5% wt/wt) (first experiment) or placed in an empty well (200 μl) of the rearing plate, to be supplied as saturated air due to evaporation (second experiment). In both experiments, a standard medium with gentamicin and an antimicrobial‐free medium were maintained as positive and negative controls, respectively. In the first experiment, in the hydrolate‐supplemented medium fewer E. larvarum completed egg‐to‐adult development than in the standard medium, but significantly more parasitoids developed from egg to adult compared to the antimicrobial‐free medium. No significant difference was found between the numbers of eggs laid by the females obtained from the standard medium vs. those from the hydrolate‐supplemented medium. In the second experiment, the hydrolate‐saturated air significantly decreased E. larvarum egg hatching, puparium formation, and female fecundity compared to the standard medium. In perspective, M. fistulosa hydrolate supplemented to the artificial media for E. larvarum may be considered as a promising candidate to replace the gentamicin solution, as suggested also by the microbiological analyses of the media, performed at various growth stages of the parasitoid in a separate trial. Conversely, the hydrolate‐saturated air treatment was deemed unsuitable. May gentamicin (a broad‐spectrum antibiotic) be replaced with hydrolate of Monarda fistulosa (Lamiaceae) in artificial media for the in vitro culture of the larval parasitoid Exorista larvarum (Diptera: Tachinidae)? In two experiments, parasitoid life‐history parameters (including the egg numbers laid by F1 females) and microbiological analyses of the media indicated that M. fistulosa hydrolate may be considered a promising candidate to replace gentamicin, if supplemented to the artificial media, not if applied via hydrolate‐saturated air.